Research on loss differences and thermal optimisation of submerged cryogenic high‐speed permanent magnet motors - Baojun Ge; Yue Wang; Xiao Xu; Likun Wang; Shuo Huang; Zhifei Yang (IET Electric Power Applications)
Abstract The utilisation of high‐speed motors in cryogenic motors achieves high efficiency and rapid transmission of cryogenic media, and at the same time, the high loss characteristic of high‐speed motors enhances the vaporisation rate of cryogenic media and reduces the transmission quality of the media. Comprehensive numerical results on power loss and thermal characteristics of a submersible cryogenic high‐speed permanent magnet motor are presented. The electromagnetic and frictional losses are calculated using precise numerical analysis, and these values are then incorporated into the fluid‐thermal coupling solution model to obtain the temperature distribution results. In order to mitigate the impact of submerged cryogenic motor temperature on low‐temperature medium vapourisation, the response surface optimisation method is employed for designing the rotor cooling diversion orifice, and determining the optimal dimensions, structure, and input conditions for flow velocity. The analysis results indicate that under low‐temperature impact, the no‐load back electromotive force increased by 9.3 V; the iron loss is increased by 22 W at rated speed and the optimised temperature is reduced by 4.3°C. A 30 kW, 12,000 rpm high‐speed permanent magnet motor is utilised for validating the numerical model and the calculated results.